Inhibitory effects of RAGE-aptamer on development of monocrotaline-induced pulmonary arterial hypertension in rats. Issue 1 (July 2021) - Nakamura, Kazufumi; Akagi, Satoshi; Ejiri, Kentaro; Yoshida, Masashi; Miyoshi, Toru; Sakaguchi, Masakiyo; Amioka, Naofumi; Suastika, Luh Oliva Saraswati; Kondo, Megumi; Nakayama, Rie; Takaya, Yoichi; Higashimoto, Yuichiro; et al.
Highlights: RAGE-aptamer suppresses development of monocrotaline-induced pulmonary arterial hypertension (PAH) in rats. Inhibition of RAGE ameliorates muscularization of small pulmonary arteries. Treatment with RAGE-aptamer might be a new therapeutic option for PAH. Abstract: Background: The receptor for advanced glycation end products (RAGE), a transmembrane receptor belonging to the immunoglobulin superfamily, is overexpressed in pulmonary artery smooth muscle cells (PASMCs) in patients with pulmonary arterial hypertension (PAH) and is implicated in the etiology of PAH. Recently, we reported that RAGE-aptamer, a short and single-stranded DNA directed against RAGE, inhibited an inappropriate increase in cultured PASMCs in PAH. The aim of this study was to determine the efficacy of RAGE-aptamer in monocrotaline-induced PAH in rats. Methods and Results: Rats were assigned to either an untreated control group, a group that received continuous subcutaneous administration of RAGE-aptamer immediately after monocrotaline injection, or a group that received control-aptamer immediately after monocrotaline injection. All rats survived 21 days after injection of monocrotaline and control-aptamer or RAGE-aptamer. Injection of monocrotaline with continuous subcutaneous delivery of control-aptamer resulted in higher right ventricular systolic pressure compared with controls. This increase was attenuated by continuous subcutaneous delivery of RAGE-aptamer. The proportion of small pulmonary arteries with full muscularization was greater in the monocrotaline and control-aptamer group than in the control group. Continuous subcutaneous delivery of RAGE-aptamer significantly reduced the percentage of small pulmonary arteries with full muscularization. Conclusions: Continuous subcutaneous delivery of RAGE-aptamer suppresses development of monocrotaline-induced PAH in rats. Inhibition of RAGE ameliorates muscularization of small pulmonary arteries. Treatment with RAGE-aptamer might be a new therapeutic option for PAH.